Development of Breast Cancer Spheroids to Evaluate Cytotoxic Response to an Anticancer Peptide - Marco Cavaco; Patrícia Fraga; Javier Valle; David Andreu; Miguel A. R. B. Castanho; Vera Neves (MDPI AG, 2021)
Breast cancer (BC) is the most commonly diagnosed cancer in women and one of the most common causes of cancer-related deaths. Despite intense research efforts, BC treatment still remains challenging. Improved drug development strategies are needed for impactful benefit to patients. Current preclinical studies rely mostly on cell-based screenings, using two-dimensional (2D) cell monolayers that do not mimic in vivo tumors properly. Herein, we explored the development and characterization of three-dimensional (3D) models, named spheroids, of the most aggressive BC subtypes (triple-negative breast cancer-TNBC; and human-epidermal growth receptor-2-HER2+), using the liquid overlay technique with several selected cell lines. In these cell line-derived spheroids, we studied cell density, proliferation, ultrastructure, apoptosis, reactive oxygen species (ROS) production, and cell permeabilization (live/dead). The results showed a formation of compact and homogeneous spheroids on day 7 after seeding 2000 cells/well for MDA-MB-231 and 5000 cells/well for BT-20 and BT-474. Next, we compared the efficacy of a model anticancer peptide (ACP) in cell monolayers and spheroids. Overall, the results demonstrated spheroids to be less sensitive to treatment than cell monolayers, revealing the need for more robust models in drug development.